2008
DOI: 10.1063/1.2839275
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark density functional theory calculations for nanoscale conductance

Abstract: We present a set of benchmark calculations for the Kohn-Sham elastic transmission function of five representative single-molecule junctions. The transmission functions are calculated using two different density functional theory (DFT) methods, namely an ultrasoft pseudopotential plane wave code in combination with maximally localized Wannier functions, and the norm-conserving pseudopotential code Siesta which applies an atomic orbital basis set. For all systems we find that the Siesta transmission functions co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 67 publications
(110 reference statements)
6
123
0
Order By: Relevance
“…Gold metal contacts to molecules has been studied the longest and given the most attention both experimentally and theoretically [2,3,4,5]. The agreement between the experimentally measured currents and the theoretically predicted currents in these systems was difficult to obtain due to the strong dependence of the conductance on the contact geometry [5,6,7,8,9,10]. The correspondence has greatly improved with the introduction of amine linkers [11,12,13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gold metal contacts to molecules has been studied the longest and given the most attention both experimentally and theoretically [2,3,4,5]. The agreement between the experimentally measured currents and the theoretically predicted currents in these systems was difficult to obtain due to the strong dependence of the conductance on the contact geometry [5,6,7,8,9,10]. The correspondence has greatly improved with the introduction of amine linkers [11,12,13].…”
mentioning
confidence: 99%
“…To calculate the room temperature conductance, we take the derivative of the current equation with respect to voltage, G = 2e h dET (E)(− ∂f ∂E ), where f is the Fermi-Dirac factor and T is the transmission probabality. The relaxation and transmission calculations are both performed using a double numeric orbital basis to avoid any discrepancies that may arise using a single numeric basis [9]. Additional details on our approach can be found in Ref.…”
mentioning
confidence: 99%
“…We have done this using the nonequilibrium Green's function (NEGF) formalism [10] as described in Refs. [11,12].…”
mentioning
confidence: 99%
“…This behavior is similar to conductance estimations in transport across molecular junctions where convergence needs to be ensured by enlarging the size of the basis set. 30,31 1. Electrical characteristics Applying our electronic transmission methodology, in this section, the electrical characteristics of SiNW based p-n-p and p-i-p junctions will be explored.…”
Section: A Transport Propertiesmentioning
confidence: 99%
“…30 Using a Wannier transformation on DFT Hamiltonians in the PW basis sets enabled them to calculate the transmission function and to compare with a NAOs transport implementation. They concluded that a double zeta polarized basis sets suffices for the particular systems.…”
Section: Introductionmentioning
confidence: 99%